Novel small molecules affecting cell membrane as potential therapeutics for avian pathogenic Escherichia coli. Issue 1 (December 2018) - Kathayat, Dipak; Helmy, Yosra; Deblais, Loic; Rajashekara, Gireesh
Abstract Avian pathogenicEscherichia coli (APEC), a most common bacterial pathogen of poultry, causes multiple extra-intestinal diseases in poultry which results in significant economic losses to the poultry industry worldwide. In addition, APEC are a subgroup of extra-intestinal pathogenicE .coli (ExPEC), and APEC contaminated poultry products are a potential source of foodborne ExPEC infections to humans and transfer of antimicrobial resistant genes. The emergence of multi-drug resistant APEC strains and the limited efficacy of vaccines necessitate novel APEC control approaches. Here, we screened a small molecule (SM) library and identified 11 SMs bactericidal to APEC. The identified SMs were effective against multiple APEC serotypes, biofilm embedded APEC, antimicrobials resistant APECs, and other pathogenicE .coli strains. Microscopy revealed that these SMs affect the APEC cell membrane. Exposure of SMs to APEC revealed no resistance. Most SMs showed low toxicity towards chicken and human cells and reduced the intracellular APEC load. Treatment with most SMs extended the wax moth larval survival and reduced the intra-larval APEC load. Our studies could facilitate the development of antimicrobial therapeutics for the effective management of APEC infections in poultry as well as otherE .coli related foodborne zoonosis, including APEC related ExPEC infections in humans.